Business Model Canvas: Shrink Swift / Siti Nurhanis Izzati Awang Nordin - Awang Nordin, Siti Nurhanis Izzati (2020)
The Business Model Canvas (BMC) is a strategic management tool to quickly and easily define and communicate a business idea or concept. It is a visual chart with elements describing a firm’s or product’s value proposition, infrastructure, customers and finances. It assists firms in aligning their activities by illustrating potential trade-offs. The nine “building blocks” of the business model design template that came to be called the Business Model Canvas were initially proposed in 2005 by Alexander Osterwalder based on his earlier work on business model ontology. The right side of the BMC focuses on the customer (external), while, the left side of the canvas focuses on the business (internal). Both external and internal factors meet around the value proposition, which is the exchange of value between your business and your customer/clients. This BMC can be used to visualize the expectations of such clients and market problems. That will enhance the market strategy and technology implementation. It can also make them more market efficient. BMC is also used to validate the market significance of products and services which in this case will be technological in nature. Projects of technology are often solutions or processes which solve a technical problem. However, market implementation of such solutions also requires the problem solution to be designed to overcome not only technical barriers, but also market and business-related cost barriers, customer reach and collaborations, and those related to the practical nature of limited initial capacities within the team